Analisis Dan Perancangan Jaringan Komputer Asrama Putri Boarding School Man 1 Surakarta - Rohman . (Indonesian Journal of Networking and Security (IJNS), 2012)
Abstact : The development of technology at this present and many people needs data  processing  and the organization or educations institution for their daily activities as well. It can not separated from the computer technology which can assist and provide data management and storage easy. In an organitation such as educational institutions at all times conduct activities related to processing and storage data, it is necessary  a communication system where the data need to be processed, data storage and exchage of  information between each other can be done quickly and efficiently. The Dormitory Boarding School MAN 1 Surakarta  which is  located in Sumpah Pemuda Street ,  Banjarsari Surakarta region have not apply integrated computer  network system. The data collection conducted by teacher  from one computer to another computer has many obtacles. This is because all computers are not able to make sharing data  and some importants data storage in each teacher’s computer  privately well as. With the above authors intend to design computer networks in Dormitory  Boarding School MAN 1 Surakarta. The design is made, because of the difficulty of retrieval of  data from one computer to another. With this design, we hope that the teacher  can retrieve and get the data easier. The purpose of this design is to make a planning of computer network system design. The research methodology used  observation, literature, interviews, analysis, planning. The results of this design is expected to give reference and tools for  the  Dormitory Boarding School MAN 1 Surakarta to build the computer network system design easy to implement  in near the future. Keywords : computer  network, sharing data   Abstrak : Di Aera teknologi dan globalisasi sekarang ini perkembangan dunia  dibidang teknologi informasi yang begitu cepat sehingga hal ini mempengaruhi perkembangan dan perubahan dalam   kehidupan masyarakat dunia dan salah  satu teknologi yang terus berkembang saat ini adalah teknologi komputer. Dengan kehadiran komputer maka dapat  membantu manusia dan  mempermudah menyampaikan informasi, mengirim berita, mendapatkan informasi data dari berbagai komputer  yang dibutuhkan dengan mudah dan cepat. Asrama Putri Boarding School MAN 1 Surakarta salah satu lembaga yang bergerak dalam bidang  pendidikan belum menerapkan sistem  jaringan komputer yang baik sehingga dalam pengambilan dan pengecekan data terutama tentang kasus dan pelanggaran siswa yang dilakukan oleh dewan Asatidz dari komputer satu ke komputer yang lain mengalami banyak hambatan. Ini disebabkan karena komputer yang ada belum dapat melakukan sharing data. Dengan hal tersebut diatas penulis bermaksud untuk merancang jaringan komputer pada di Asrama Putri Boarding School MAN 1 Surakarta. Perancangan ini dilakukan karena sulitnya pengambilan data dari satu komputer ke komputer yang lain. Dengan perancangan ini dapat memberikan kemudahan dan keefektifan dan pengambilan data tersebut. Dalam penelitian ini menggunakan observasi, kepustakaan, interview, analisa, dan perencanaan. Hasil yang diharapkan adalah memberikan gambaran dan acuan  Asrama Putri Boarding School MAN 1 Surakarta untuk membangun sistem jaringan komputer yang dapat diimplementasikan dimasa mendatang. Kata kunci : Jaringan Komputer, sharing data